The evaluation and application of multilocus variable number tandem repeat analysis (MLVA) for the molecular epidemiological study of Salmonella enterica subsp. enterica serovar Enteritidis infection. Issue 1 (December 2016) - Liu, Yao; Shi, Xiaolu; Li, Yinghui; Chen, Qiongcheng; Jiang, Min; Li, Wanli; Qiu, Yaqun; Lin, Yiman; Jiang, Yixiang; Kan, Biao; Sun, Qun; Hu, Qinghua
Abstract Background Salmonella enterica subsp.enterica serovar Enteritidis (S. Enteritidis) is one of the most prevalentSalmonella serotypes that cause gastroenteritis worldwide and the most prevalent serotype causingSalmonella infections in China. A rapid molecular typing method with high throughput and good epidemiological discrimination is urgently needed for detecting the outbreaks and finding the source for effective control ofS . Enteritidis infections. Methods In this study, 194 strains which included 47 from six outbreaks that were well-characterized epidemiologically were analyzed with pulse field gel electrophoresis (PFGE) and multilocus variable number tandem repeat analysis (MLVA). Seven VNTR loci published by the US Center for Disease Control and Prevention (CDC) were used to evaluate and develop MLVA scheme forS. Enteritidis molecular subtyping by comparing with PFGE, and then MLVA was applied to the suspected outbreaks detection. AllS. Enteritidis isolates were analyzed with MLVA to establish a MLVA database in Shenzhen, Guangdong province, China to facilitate the detection ofS . Enteritidis infection clusters. Results There were 33 MLVA types and 29 PFGE patterns among 147 sporadic isolates. These two measures had Simpson indices of 0.7701 and 0.8043, respectively, which did not differ significantly. Epidemiological concordance was evaluated by typing 47 isolates from six epidemiologically well-characterized outbreaks and it did not differ for PFGE and MLVA. We applied the well established MLVA method to detect twoS. Enteritidis foodborne outbreaks and find their sources successfully in 2014. A MLVA database of 491S. Enteritidis strains isolated from 2004 to 2014 was established for the surveillance of clusters in the future. Conclusions MLVA typing ofS. Enteritidis would be an effective tool for early warning and epidemiological surveillance ofS. Enteritidis infections.